Examining the Relationship Between Foreign Ownership, Environmental Performance, Firm Size, and Corporate Social Responsibility Disclosure - Hanifah, Apriliyah Nur; Umaimah, Umaimah (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
Many companies often overlook their social responsibility, failing to recognize its crucial  role  in  enhancing  their  reputation.  In  the  current  corporate  landscape, companies   are   increasingly   focusing   on   capital   development   while   also addressing  environmental  concerns.  Greater  attention  is  being  directed  toward the   surrounding   environment,   as   it   can   significantly   influence   corporate operations and outcomes.This study aims to evaluate the relationship between foreign ownership, environmental performance, and firm size with the disclosure of  Corporate  Social  Responsibility  (CSR).  The  research  targets  manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2023 period. A total of 40 samples were selected using the  purposive sampling  method. The data analysis was conducted using multiple linear regression, employing SPSS as the analytical tool.The findings indicate that foreign ownership does not have a significant  effect  on  CSR  disclosure.  Similarly,  firm  size  is  not  significantly associated    with    CSR    disclosure.    However,    environmental    performance demonstrates a significant influence on the scope of CSR disclosure. These results suggest  that  companies  should  prioritize  environmental  performance  as  a  key driver  of  CSR  initiatives.  This  study  underscores  the  importance  of  Corporate Social  Responsibility  as  a  means  for  businesses  to  positively  engage  with  and influence their surrounding environment.